Recurrence of Disease Following Liver Transplantation: Nonalcoholic Steatohepatitis vs Hepatitis C Virus Infection - A Hanouneh; C Macaron; R Lopez; AE Feldstein; L Yerian; B Eghtesad; NN Zein (International Journal of Organ Transplantation Medicine, 2011)
AbstractBackground: Nonalcoholic steatohepatitis (NASH) is an increasing indication for orthotopic liver transplantation (OLT) in the United States and other countries. However, the incidence of disease recurrence and natural course following OLT remains incompletely understood.Objective: To estimate the incidence of recurrent disease, outcome and identify risk factors associated with disease recurrence in patients undergoing OLT for NASH as compared to those undergoing OLT for HCV cirrhosis.Methods: We identified all patients with end-stage liver disease secondary to NASH (n=53) or HCV (n=95) cirrhosis who underwent OLT at our institution between 1998 and 2005. Protocol liver biopsies were performed (Day 7, Month 4 and yearly) after OLT, and as clinically indicated. Kaplan-Meier survival analysis was performed to assess the fibrosis progression and survival. Cox regression analysis was performed to identify factors associated with disease recurrence.Results: Five-year survival was 90.5% in NASH vs 88.4% in HCV group (p=0.97). The median (25%ile, 75%ile) follow-up to last available biopsy was 12.7 (5.9, 26.3) months, during which 17 (32%) of NASH patients developed persistent fatty infiltration in their graft, 8 (15%) of whom had accompanying histologic features of recurrent NASH. There was no difference in the prevalence of post-OLT steatosis between HCV and NASH patients after adjusting for time of histologic follow-up (p=0.33). Patients with HCV infection were more likely to develop hepatic fibrosis post-OLT than those with NASH (62.1% vs 18.9%, p<0.001). Multivariate analysis identified post-OLT diabetes (HR=2.0, 95% CI: 1.2–3.2, p=0.007) as an independent risk factor for fibrosis development. Additionally, NASH subjects who received steroids had a significantly higher risk of developing hepatic fibrosis post-OLT than NASH patients who did not receive steroids and all HCV subjects (p<0.001).Conclusion: Recurrence of steatosis post-OLT is common. Corticosteroid use may contribute to fibrosis progression in this population.